Detection of Uropathogenic Specific Protein Gene (usp) and Multidrug Resistant Bacteria (MDR) of Pathogenic Escherichia coli Isolated from Baghdad City - Khalaf, Zainab Zamel; Flayyih, May Talib (Iraqi Journal of Science, 2024)
Escherichia coli is gram negative bacteria and represents a typical resident of the digestive systems of both humans and animals. The stability and equilibrium of the luminal microbial flora are significantly influenced by E. coli. The Escherichia coli uropathogenic-specific protein (Usp) represents type of genotoxins produced by uropathogenic E. coli rather than fecal E. coli isolates. In the current study E. coli was isolated from urine and stool and usp gene was detected in it. Sensitivity test was evaluated by using different types of antibiotics and the usp gene was detected by PCR in all bacterial isolates. Antibiotics sensitivity test showed variable degrees of sensitivity and resistance. High percentage of sensitivity was achieved against amikacin (86%) and that for ciprofloxacin, ceftazidime, gentamicin and tobramycin it was 80%. Whereas trimethoprim and aztreonam showed 64% and 60% sensitivity respectively. In this study, most isolates were resistant to amoxicillin 92%; while they showed different degrees of resistance against other types of antibiotics (from tetracycline 62% to amikacin 4%). The frequency of multi drug resistant (MDR) bacteria was about 64 % (32 isolates), 30 from urine and 2 from the stool. The results showed that usp gene was found in 26 bacterial isolates (52%), whereas other 24 (48%) isolates didn’t have this gene. It was concluded that source of bacterial isolates carry usp gene was urine, with the exception of one isolate from f stool, and E. coli recorded as multidrug resistant bacteria (MDR).